Distribusi Logam Kadmium dalam Air dan Sedimen di Sungai Musi Kota Palembang - Emilia, Ita; Suheryanto, Suheryanto; Hanafiah, Zazili (Jurnal Dosen Universitas PGRI Palembang)
AbstractThis aims of this research is to determine of cadmium in water and sediment Musi River Palembang. Technical method sampling by purposive. Data collected from eight sample point and determination of cadmium contaminant using by AAS methode. The results a averageof cadmium (Cd) is0.0091mg/Lwith a range 0.0021-0.0137mg/L,and lower from threshold of PERDA the South Sumatra No.16of 2005. The average of cadmium (Cd) sediments is.1520mg/kg with range 0.1000-0.1890mg/kg, and lower from threshold of Dutch Quality Standards for Metalsi sediment.Keywords: distribution , cadmium , water , sediment , Musi river